Foreign Direct Investment and Youth Employment Causality: Evidence From ASEAN-5 Countries - Axellina Muara Setyanti; Setyo Tri Wahyudi (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: FDI - employment relationship has been a major concern of many researchers due to it's various findings. FDI is stated that able to trigger growth in employment, however, on the other hand, some have found that employment conditions affect FDI inflow. Meanwhile, several studies found a bidirectional relationship, or even no-relationship. With a focus on youth employment, this study aimed to examine the link between FDI and youth employment in ASEAN-5 countries. From the results of the Granger Causality test, it was found that in Indonesia, Malaysia, Philippines, and Singapore the FDI inflow is leading to youth employment, while in Thailand, the relationship is vice versa. Overall, there is no bidirectional causal relationship between FDI and youth employment in ASEAN-5 countries.Keywords: Foreign Direct Investment, Youth Employment, Granger Causality, ASEAN-5 Kausalitas Penanaman Modal Asing dan Penyerapan Tenaga Kerja Muda: Bukti dari Negara-negara ASEAN-5Abstrak: Keterkaitan antara FDI dan penyerapan tenaga kerja telah menjadi perhatian utama banyak peneliti karena temuan yang beragam. FDI dinyatakan dapat memicu pertumbuhan lapangan kerja, namun di sisi lain, beberapa peneliti menemukan bahwa kondisi ketenagakerjaanlah yang mempengaruhi arus masuk FDI. Sementara itu, beberapa penelitian lain menemukan adanya hubungan dua arah, atau bahkan tidak ada hubungan. Dengan fokus pada penyerapan tenaga kerja muda, penelitian ini bertujuan untuk mengkaji hubungan antara FDI dan penyerapan tenaga kerja muda di negara-negara ASEAN-5. Dari hasil uji kausalitas Granger ditemukan bahwa di Indonesia, Malaysia, Filipina, dan Singapura, aliran FDI yang masuk mengarah pada pada penciptaan lapangan kerja bagi kaum muda, sedangkan di Thailand ditemukan hubungan yang sebaliknya. Secara keseluruhan, tidak ditemukan hubungan kausal dua arah antara FDI dan penyerapan tenaga kerja muda di negara-negara ASEAN-5.Kata kunci: Penanaman Modal Asing, Penyerapan Tenaga Kerja Muda, Kausalitas Granger, ASEAN-5